Phytophthora theobromicola sp. nov.: A New Species Causing Black Pod Disease on Cacao in Brazil - Decloquement, Jennifer; Ramos-Sobrinho, Roberto; Elias, Samuel Galvão; Britto, Dahyana Santos; Puig, Alina Sandra; Reis, Ailton; da Silva, Rildo Alexandre Fernandes; Honorato-Júnior, Jaime; Luz, Edna Dora Martins Newman; Pinho, Danilo Batista; Marelli, Jean-Philippe (Frontiers in Microbiology, 2021)
Black pod disease, caused by Phytophthora species, is among the main limiting factors of cacao (Theobroma cacao L.) production. High incidence levels of black pod disease have been reported in Brazil, being induced by P. capsici, P. citrophthora, P. heveae, and P. palmivora. To assess the diversity of Phytophthora species affecting cacao in Brazil, 40 new isolates were obtained from cacao pods exhibiting symptoms of black pod disease collected in different smallholder farms in 2017. Ten cacao-infecting isolates morphologically identified as P. citrophthora and P. palmivora were molecularly characterized.The genomic regions beta-tubulin, elongation factor 1 alpha, heat shock protein 90, and internal transcribed spacer, and the mitochondrially encoded cytochrome c oxidase I and II genes were obtained from the Phytophthora isolates. The morphological characterization and evaluation of the mycelial growth rates for the Phytophthora isolates were performed in vitro. Based on the molecular analysis and morphological comparisons, 19 isolates were identified as P. palmivora (clade 4). Interestingly, 31 isolates grouped together in the phylogenetic tree and were placed apart from previously known species in Phytophthora clade 2..Therefore, these isolates are considered as a new species herein referred to as Phytophthora theobromicola sp. nov., which produced papillate, semipapillate and persistent sporangia on simple sporangiophores. The P. palmivora isolates were identified as A1 mating type by pairing each isolate with known A1 and A2 tester strains of P. capsici, but no oogonia/antheridia were observed when P. theobromicola was paired with the different tester strains. The P. theobromicola and P. citrophthora isolates showed higher mycelial growth rates, when compared to P. palmivora, on different media at 10, 15, and 20°C. However, similar values were observed when grown on clarified CA media at 25 and 30°C. The pathogenicity tests carried out on pods of four cacao clones (CCN51, PS1319, Cepec2004, and CP49) showed significant variability among the isolates of both Phytophthora species, with P. theobromicola inducing higher rates of necrotic lesion expansion, when compared to P. palmivora. This is the first report of Phytophthora theobromicola on T. cacao. These findings are crucial to improve the disease control strategies, against Phytophthora sp infecting T. cacao.